Greco-Gauchos: National Regeneration and Fascist Hellenism in Leopoldo Lugones - Outes-León, Brais (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2025)
This study explores the centrality of Hellenism within the political evolution towards authoritarianism of Argentine intellectual Leopoldo Lugones (1874-1938). Starting with his vindication of the Hellenist filiation of Argentina in El payador (1916) as a foundational myth of national identity, this analysis shows how the discursive articulation of a Fascist Hellenism comes to full fruition in Estudios helénicos (1924) and Nuevos estudios helénicos (1928). By combining philology and political discourse, in these two volumes Lugones articulates a Fascist project of national regeneration that vindicates the masculine and militaristic values of Homeric epic heroism as antidote against liberal democracy.